Patellar Bone–Tendon–Bone Autografts versus Quadriceps Tendon Allograft with Synthetic Augmentation in a Canine Model - Smith, Patrick A.; Stannard, James P.; Bozynski, Chantelle C.; Kuroki, Keiichi; Cook, Cristi R.; Cook, James L. (The Journal of Knee Surgery, 2019)
Patellar bone–tendon–bone (pBTB) autografts are often considered the “gold standard” for complete anterior cruciate ligament (ACL) reconstruction and are also associated with significant complications and early-onset knee osteoarthritis (OA). A novel quadriceps tendon allograft with synthetic augmentation, or “internal brace” (QTIB), has been reported to have potential advantages for ACL reconstruction based on animal model data. In this preclinical canine comparison study, we hypothesized that QTIB allograft compared with pBTB autograft would provide superior durability for knee stability, function, and prevention of OA. Under approval from our Institutional Animal Care and Use Committee, adult purpose-bred research hounds (n = 10) underwent arthroscopic complete transection of the ACL followed by either an arthroscopic-assisted all-inside ACL reconstruction using the QTIB allograft (n = 5) or pBTB autograft (n = 5). Contralateral knees were used as nonoperated controls (n = 10). Radiographic and arthroscopic assessments were performed at 2 and 6 months, respectively, after surgery. Anterior drawer, internal rotation, lameness, kinetics, pain, effusion, and comfortable range of knee motion were measured at 2, 3, and 6 months. Biomechanical and histologic assessments were performed at 6 months. All reconstructed knees were stable and had intact ACL grafts 6 months after surgery. At 6 months, QTIB reconstructed knees had significantly less lameness, lower pain, less effusion, and increased range of motion when compared with BTB knees (p < 0.05). BTB knees had significantly higher radiographic OA scores than QTIB knees at 6 months (p < 0.05). Superior outcomes associated with QTIB allograft may be due to the lack of donor site morbidity, the use of a robust tendon graft, and/or protection of the graft from the synthetic augmentation. Robust tendon grafts combined with a synthetic internal brace and platelet-rich plasma (PRP) may allow for more rapid and robust tendon–bone healing and graft “ligamentization,” which protects the graft from early failure and rapid OA development that can plague commonly-used allografts.
Keywords: anterior cruciate ligament; autograft; allograft; canine; arthroscopy; animal model